School Safe Route in Sumbersari District, Jember Regency - Mutiah, Asna Malikhatul; Kriswardhana, Willy; Hasanuddin, Akhmad (Semarang State University, 2021)
The number of underage accidents in Jember Regency in 2011-2012 increased from 37 to 190 cases. Therefore, bicycle and pedestrian paths were planned through the School Safe Route program that could encourage students to choose to ride a bicycle or walking. The method of this study was the Level of Service analysis (LOS), student and travel characteristics, cross tabs, bicycle lanes, pedestrians, and road equipment facilities. The results showed that the level of road service on each road section varied, including LOS A, B, D and E. The characteristic and common cross tabs analysis results showed that most transportations used by students were motorcycles. Still, there was a relatively large proportion of students’ willingness to change their transportation mode in operational conditions if bicycle and pedestrian path facilities were provided. Cycle path analysis showed that the types of bicycle lanes were planned, specifically type A and C, with a bicycle lane width was 1.44 m for each lane. From the calculation of the minimum effective width of the sidewalk obtained 1.01 m with a crossing facility in the form of a pelican crossing with waiting stalls. Several road equipment facilities were planned, such as traffic signs, road markings and Traffic Signaling Equipment (TSE). Bicycle and pedestrian routes were planned at Tawang Mangu Street, Danau Toba Street, Mastrip Barat Street, Kalimantan Street, Jawa Street, Karimata Street, M.T. Haryono Street, Letjen S. Parman Street, Letjen Panjaitan Street and Letjen Suprapto Street.